Gynecological Malignancies Managed in The Institute of Nuclear Medicine and Oncology, Wadmedani-Sudan During 1999-2005 - Omer Abuidris, Dafalla; Mohammed Ibnoof, Rehab Sid-Ahmed; Mohamed Elsanousi, Mohamed Elsanousi; Abdalla Eltayeb, Elgaylani; Mohamed El Gaili, Elgaili (Gezira Journal of Health Sciences, 2008)
Introduction : Gynecological malignancies (GMs) are one of the most prevalent cancers in Africa. Objective of this work is to review data of patients with GMs treated in Institute of Nuclear Medicine, Molecular Biology and Oncology (INMO)-University of Gezira -Wadmedani- Sudan, and reflect on characteristics of GMs in Central Sudan. Material and Methods : A retrospective hospital-based descriptive study was conducted to review GMs patients records treated in INMO from year 1999-2005. Analysis included age, residence, stage, topography and morphology of the cancer. Results : During study period GMs constituted about 20.5 percent of all women malignancies and it is the second commonest female cancer preceded by breast (36.7%). Most of the patients were housewives from rural areas of Gezira and nearby States.  The sites were ovary, 41%, cervix, 34%, uterus, 13.8%, uterine choriocarcinoma, 7.9%, vulva cancer, 2.9% and no single case of vaginal carcinoma was reported. The mean age of all patients was 52.45 years, Median age for ovarian cancer was, 50, cervix 55, uterus 55, Choriocarcinoma of the uterus 35 and vulva 60 years of age. Almost all varieties of histopathological types were seen. Fifty eight percent of patients presented with stage III & IV. Conclusions : GMs are common and present in late stages. The commonest GMs was ovarian cancer which affect relatively young patients. Cervix was the second common site and affect relatively older age group. Vulvar cancer was relatively rare and vaginal cancer was not seen. For the improvement of the outcome early detection, management guidelines and financial support are highly recommended.